A China pode afetar a transiç\~ao energética na América Latina? Uma análise a partir do índice de transiç\~ao energética do Fórum Econômico Mundial - Carlos Renato Ungaretti; Marco Aurélio Alves de Mendonça; Ticiana Gabrielle Amaral Nunes (Instituto de Pesquisa Econômica Aplicada (IPEA), 2025)
– The objective of this work was to explore energy transition trajectories in China and Latin America, indicating their synergies and potential. Starting from a description of the Energy Transition Index (ETI) and an explanation of its methodology, we sought to map the global energy transition, emphasizing its challenging momentum and the imperative of its acceleration. In this sense, strategies that can be designed and implemented for the decarbonization of energy systems were identified, and the importance of international cooperation was highlighted. Given national and regional particularities, the evolution and perspectives of the energy transition in China and Latin America were observed, especially with regard to the dimensions of equity, security, and sustainability. It was argued that China can constitute a key ally for the energy transition in Latin America, contributing to reducing investment gaps, diversifying energy systems, and developing green industries.
Keywords: Q01; Q48; Q56; Q58; F02; F6; F15; F35; 330; China; America Latina; energy transition; Energy Transition Index; investments